Exceptional response to chemo-immunotherapy in a patient with HER2-negative, TMB-high metastatic gastric mucinous adenocarcinoma: a case report and literature review - Liu, Caiqi; Li, Xiangxue; Qi, Qi; Jing, Fanjing; Lv, Jing; Qiu, Wensheng; Wang, Shasha (Frontiers in Immunology, 2026)
Gastric mucinous adenocarcinoma (GMC) is a rare subtype of gastric cancer characterized by excessive mucus production, aggressive biological behavior, and poor prognosis, with most patients presenting with metastatic disease at initial diagnosis and losing the opportunity for curative resection. Currently, there are no standardized diagnostic and treatment guidelines for metastatic GMC in the conversion therapy setting, and the therapeutic effect of conventional chemotherapy remains unsatisfactory. Herein, we present a 69-year-old male patient diagnosed with HER2-negative, TMB-H advanced GMC, with intraperitoneal and retroperitoneal lymph node metastases. The patient was initially deemed unresectable by the multidisciplinary team (MDT) but opted for conversion therapy due to a strong willingness for treatment and good performance status (ECOG-PS=0). He received 6 cycles of FLOT chemotherapy combined with nivolumab, achieving partial response (PR) per RECIST 1.1. Subsequent laparoscopic distal gastric subtotal resection (D2+ lymphadenectomy) was performed, and postoperative pathology revealed a near pathological complete response (Mandard-TRG1) with no lymph node metastases (0/21), pathologically staged as ypTisN0. Postoperatively, the patient received 4 cycles of XELOX chemotherapy plus nivolumab, followed by consolidative radiotherapy synchronized with capecitabine and nivolumab, and subsequent maintenance therapy with capecitabine and nivolumab until sustained no evidence of disease (NED) was confirmed in January 2023. Regular surveillance, including the latest contrast-enhanced CT in May 2025, showed no recurrence or metastasis, with progression-free survival (PFS) exceeding 5 years. This exceptional and sustained response may be attributed to the synergistic effect of TMB-H and POLD1 mutation, which enhance neoantigen generation and sensitize tumors to immunotherapy. This case highlights the potential of biomarker-driven chemo-immunotherapy combined with MDT-guided multimodal treatment (surgery + adjuvant therapy + consolidative radiotherapy) to achieve curative intent in patients with metastatic GMC, providing valuable insights for personalized treatment strategies in this poor-prognosis population.